Evans Syndrome (Journal of Medicine, 2010)
Evans' syndrome is a rare autoimmune disorder in which the body makes antibodies that destroy the red blood cells, platelets and white blood cells. Patients are diagnosed with thrombocytopenia and Coombs' positive haemolytic anaemia and have no other known underlying aetiology. We report two cases of autoimmune haemolytic anaemia (AIHA) associated with immune thrombocytopenia which is known as Evans's syndrome. In these patient there were clinical evidence of haemolysis, serum bilirubin was elevated, blood film showed anaemia with trrombocytopenia but no spherocytosis. Immunosuppression was achieved with steroid. We would like to highlight that a negative Coomb's test is now often interpreted as absence of autoantibodies, but it is more or less preclusive for the diagnosis of AIHA. Keywords: Evan's Syndrome, autoimmune haemolytic anaemia DOI:10.3329/jom.v11i1.4280 J Medicine 2010: 11: 78-82